1989
DOI: 10.1159/000281479
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Determination of the Residual Bladder Volume

Abstract: In a clinical study the ultrasonic determination of the residual bladder volume is evaluated by applying several echographic methods described in the literature. 163 patients (age 3–89 years, 114 males and 49 females) and 13 students were examined. Only in the latter group the bladder volume was also determined by a planimetric method. The most practical method showed a good agreement (with a maximum deviation of 25%) between the ultrasonically measured volumes and the volumes measured by catheterization in 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Also, we would have to establish the cutoff point for moving from one formula to another. We agree with Hendrix et al [21] that it is inappropriate to compare results of various studies for the following reasons.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Also, we would have to establish the cutoff point for moving from one formula to another. We agree with Hendrix et al [21] that it is inappropriate to compare results of various studies for the following reasons.…”
Section: Discussionsupporting
confidence: 83%
“…(2) There are differences in image quality among the various companies producing ultrasonographic equip ment, depending upon the the type and stage of develop ment [21], (3) There are differences in sample populations. Braun and Hofman [22] made a comparative investiga tion of different methods on the same population.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors found that ultrasonic assessment of bladder volume was not accurate enough to replace catheterisation [8]. Insufficient accuracy has been ascribed to poor images of the bladder and large variations in bladder shape [6]. Lower volumes give poorer images and are less accurate [6].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient accuracy has been ascribed to poor images of the bladder and large variations in bladder shape [6]. Lower volumes give poorer images and are less accurate [6]. To improve accuracy some authors proposed new scanning methods such as transvaginal [9] or transrectal application [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation